The NLRP3 inflammasome contributes to host protection during Sporothrix schenckii infection. Issue 2 (3rd March 2017) - Gonçalves, Amanda Costa; Ferreira, Lucas Souza; Manente, Francine Alessandra; de Faria, Carolina Maria Quinello Gomes; Polesi, Marisa Campos; de Andrade, Cleverton Roberto; Zamboni, Dario Simões; Carlos, Iracilda Zeppone
Summary: Sporotrichosis is a mycosis caused by fungi from the Sporothrix schenckii species complex, whose prototypical member is Sporothrix schenckii sensu stricto . Pattern recognition receptors (PRRs) recognize and respond to pathogen‐associated molecular patterns (PAMPs) and shape the following adaptive immune response. A family of PRRs most frequently associated with fungal recognition is the nucleotide‐binding oligomerization domain‐like receptor (NLR). After PAMP recognition, NLR family pyrin domain‐containing 3 (NLRP3) binds to apoptosis‐associated speck‐like protein containing a caspase recruitment domain (ASC) and caspase‐1 to form the NLRP3 inflammasome. When activated, this complex promotes the maturation of the pro‐inflammatory cytokines interleukin‐1 β (IL‐1 β ) and IL‐18 and cell death through pyroptosis. In this study, we aimed to evaluate the importance of the NLRP3 inflammasome in the outcome of S. schenckii infection using the following three different knockout (KO) mice: NLRP3 −/−, ASC −/− and caspase‐1 −/− . All KO mice were more susceptible to infection than the wild‐type, suggesting that NLRP3‐triggered responses contribute to host protection during S. schenckii infection. Furthermore, the NLRP3 inflammasome appeared to be critical for the ex vivo release of IL‐1 β, IL‐18 and IL‐17 but not interferon‐ γ . Additionally, a role for the inflammasome in shaping the adaptive immune response was suggested by the lower frequencies of type 17 helper T (Th17) cells and Th1/Th17 but not Th1 cells in S. schenckii ‐infected KO mice. Overall, our results indicate that the NLRP3 inflammasome links the innate recognition of S. schenckii to the adaptive immune response, so contributing to protection against this infection. Abstract : The NLRP3 inflammasome has a protective role in the Sporothrix schenckii infection and this may be linked to interleukin‐1 β and interleukin‐17 production.